The Double-Trump Decision Management Model in Global Exchange - Rutkauskas, Aleksandras Vytautas (Ekonomika, 2005)
The main goal of the article is to reveal the content of the so-called “double trump” decision management model in the global currency market and to present possibilities and results of its practical application. This model is developed on the basis of the author’s earlier proposed model of adequate investment decision evaluation portfolio, and it was experimentally implemented with the aid of a special currency rate change forecasting system using the FOREX global currency rate market data. The investigation was carried out using real FOREX data for the period from 11 December 2004 to 10 October 2005. The conceptual aim of the article is to broaden the discussion about financial market efficiency by testing market efficiency theory not through an attempt to defeat the market. but through proving market homogeneity, i.e. proving that there are always non-efficiency shoals in the market. when it is possible to elaborate a decision strategy allowing an advantage over the real market decisions over a rather long period of time. The pragmatic aim of the research is to find the possibilities and means of decision management in the currency market strategies advantageous over particular market decisions in general. Continuous development and practical use of such strategies should help in forming market intelligence.